PENGARUH KOMUNIKASI INTERPERSONAL TERHADAP PROSES TRANSFER PENGETAHUAN USAHATANI JAGUNG DARI PETANI TUA KE PETANI MUDA DI DESA UMBA KECAMATAN NAPANO KUSAMBI KABUPATEN MUNA BARAT - Nilmalasari, Nilmalasari; Wunawarsih, Ima Astuty; Buana, Tjandra; Dima, Darsilan (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2026)
Interpersonal communication is a critical component of the knowledge transfer process, particularly within the context of farming. In the agricultural sector, effective communication has been identified as a key factor in facilitating the transfer of knowledge from experienced farmers to their successors. This transfer is particularly important in the context of corn farming, where the dissemination of best practices is crucial for enhancing productivity and environmental sustainability. The challenge of fostering effective communication between farmers has led to a dearth of understanding regarding strategies for enhancing agricultural practices. The objective of this study is to examine the impact of interpersonal communication on the process of knowledge transfer regarding corn farming from older farmers to younger farmers in Umba Village, Napano Kusambi District, West Muna Regency. The present study employed a quantitative approach, utilizing a survey method. The research population comprised all 33 young farmers residing in Umba Village, and the sampling technique employed was a census. The data were collected through a variety of methods, including surveys, interviews, literature reviews, and documentation. The research variables were interpersonal communication and the process of corn farming knowledge transfer. The analysis was executed through the implementation of both descriptive and inferential statistics. The findings indicated that interpersonal communication exerted a substantial influence on the efficacy of the transmission of corn farming knowledge between generations of farmers. The presence of openness, empathy, supportive attitudes, positive attitudes, and equality in social interactions fostered the exchange of experiential knowledge between older and younger farmers. Empirical analysis demonstrates that the efficacy of knowledge transfer processes is contingent upon the quality of interpersonal communication. These processes are most effective when communication is of a high caliber, which is evident in all stages of the knowledge transfer process, including initiation, involvement, rumination, and integration in corn farming. The transfer of knowledge in the agricultural sector is not purely technical in nature; rather, it is significantly influenced by the relational and social dimensions inherent in interactions between agricultural actors. Strengthening interpersonal communication between generations of farmers is a strategic element in efforts to regenerate farmers and ensure the sustainability of the corn farming system, and needs to be systematically integrated into the formulation of rural agricultural development policies and programs.